Optimal scheduling of a pumped storage hydro unit in the day-ahead and secondary reserve electricity market - Lagarto, João (2019)
Ancillary services play a major role in power systems security and stability. The transmission systems operators contract some of these services at minimum cost in competitive markets. This is the case of the secondary reserve market (SRM). Besides the day-ahead market (DAM) generating companies, aiming at maximize their profits, can increase their revenues by selling available capacity in the SRM. This paper presents the solution of a price-taker generating company, owning a pumped-storage hydro (PSH) unit, acting in DAM and SRM. The results were obtained for three case studies: the generating company acts only in the DAM; the generating company acts in both markets with a fixed pumping capacity of the PSH unit; the generating company acts in both markets with a variable pumping capacity of the PSH unit. Results show that higher profits are obtained when acting in both markets with a variable pumping capacity of the PSH unit.